Aggregative Growth of Oligopeptide‐Protected Gold Nanoclusters into Plasmonic Particles. Issue 2 (19th January 2022) - Zheng, Zhiren; Hu, Yanyan; Lv, Ying; Liu, Lu; Fan, Daoqing; Zhang, Lichao; Chen, Ling; Yu, Haizhu; Zhu, Manzhou
Abstract: The stimuli response of nanomaterials represents a highly appealing characteristic, whereas the practical applications (in catalysis, biosensing etc.) are largely restricted by the limited understanding on the recognition mechanism. Herein, we report a pH‐regulated size evolution from atomically precise Au nanoclusters (NCs) to plasmonic nanoparticles (NPs). The spectral monitoring demonstrates a three‐stage aggregative growth pathway. First, the non‐covalent interactions among the exterior oligopeptide ligands are gradually enhanced with the increased alkalinity, and then the Au−S bonding is partially disrupted, with the exposed Au atoms aggregating to form relatively larger, polydisperse clusters under weak alkaline conditions. Finally, size‐redistribution occurs slowly under strong alkaline conditions to form the plasmonic particles. The controllable transition sheds light on the transition characteristics from molecular state to metallic state of Au nanomaterials. Abstract : This study reports the mechanism of a pH‐regulated evolution from oligopeptide‐protected gold nanoclusters to plasmonic particles, and the main driving force is the noncovalent interactions of exterior ligands under alkaline condition.